2017
DOI: 10.20396/bjos.v15i2.8648755
|View full text |Cite
|
Sign up to set email alerts
|

Tooth whitening recovers the color of pre-stained composites

Abstract: Aim: To assess the effect of home-whitening on aged and stained composite. Methods: Fifteen discshaped specimens (10 mm diameter x 2 mm thick) of Filtek Z350XT, shade A2E were fabricated, polished and embedded in wax, leaving exposed the top surface. The specimens were allocated to three groups (n=5): A -the specimens remained dry; B -conditioning in distilled water and; C -conditioning in distilled water and coffee. They were next subjected to whitening with 10% carbamide peroxide (Whiteness Perfect) for 4 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The color of tooth-colored restorations is usually a concern after tooth whitening, requiring a restoration replacement after tooth whitening is finished 13 . Recent studies showed that perceptible color change (∆E*) might be induced by tooth whitening substances when extrinsically acquired stains are impregnated in the restoration 12,25 . However, lower thresholds were set recently for 50%:50% perceptibility and acceptability of color change.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The color of tooth-colored restorations is usually a concern after tooth whitening, requiring a restoration replacement after tooth whitening is finished 13 . Recent studies showed that perceptible color change (∆E*) might be induced by tooth whitening substances when extrinsically acquired stains are impregnated in the restoration 12,25 . However, lower thresholds were set recently for 50%:50% perceptibility and acceptability of color change.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the presence of 2.5% hydrogen-peroxide in Listerine Whitening Extreme did not play a role in color change, producing the lowest nominal ∆E* value of all groups. This lack of significant influence of a whitening substance in the mouth rinse may again be explained by the absence of extrinsic staining agents in the composite resin 12,25 , causing minimum color changes and unlikely presenting clinical significance 25 . The overall color change was mainly driven by the reduction in a* and b* axes values, which leads to color changes towards green in the a* axis and towards blue in the b* axis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations